2016
DOI: 10.1016/j.envres.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Low-level exposure to lead, blood pressure, and hypertension in a population-based cohort

Abstract: Low-level lead exposure increases blood pressure and may increase the risk of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(52 citation statements)
references
References 24 publications
6
42
0
1
Order By: Relevance
“…• Lead: Long-term exposure to lead in adults has been associated with higher BP in population studies 295,296 and in studies of industrial workers with high lead exposure, 297 although findings have not been consistent. 298 At least 1 cross-sectional study of 122 children demonstrated that children with higher blood lead concentrations had higher BP; lower socioeconomic status was also seen in this group, which may have confounded the BP results.…”
Section: Secondary Causes: Environmental Exposuresmentioning
confidence: 99%
“…• Lead: Long-term exposure to lead in adults has been associated with higher BP in population studies 295,296 and in studies of industrial workers with high lead exposure, 297 although findings have not been consistent. 298 At least 1 cross-sectional study of 122 children demonstrated that children with higher blood lead concentrations had higher BP; lower socioeconomic status was also seen in this group, which may have confounded the BP results.…”
Section: Secondary Causes: Environmental Exposuresmentioning
confidence: 99%
“…The other important ion is lead. This ion elevated blood pressure causes sleep disturbances and anemia . Arsenic ions exists in human and animal tissues have significant toxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lead induced hypertension has been shown to occur even in the absence of symptomatic lead intoxication and even before the onset of clinically apparent renal impairment [2] [3] [4]. Several epidemiologic studies [5] [6] [7] [8] [9] have shown that relatively low level of lead exposure is associated with a significant increase in blood pressure. This epidemiological association of lead exposure and elevated blood pressure has been shown to contribute largely to the disease burden attributable to lead, as a result of its associated cardiovascular risk [10] [11].…”
Section: Introductionmentioning
confidence: 99%